Medial rectus resection versus plication in basic type intermittent exotropia - Hanan S. Hegazy; Mona N. Mansour (Journal of the Egyptian Ophthalmological Society)
Purpose To compare the efficacy of unilateral recession-resection (RR) versus unilateral recession-plication (RP) in basic-type intermittent exotropia (X (T)). Patients and methods A prospective study included 27 patients, aged 10–45 years with a diagnosis of basic type of X (T), divided into two groups: group I (14 patients) underwent RR and group II (13 patients) underwent RP, follow-up period was 3 months following surgery. Successful outcome defined as postoperative exophoria/exotropia less than 10 Prism diopters (PD) to esophoria/esotropia less than 5 Prism diopters. Results Postoperative, the success rate was 71.43% in group I and 76.92% in group II, without significant difference (P=0.683). Patients with fair and good control of deviation preoperatively had more chances of success than patients with preoperative poor control (OR=12.0, 95% CI = 1.482–97.179, P=0.020), other factors including the age, preoperative angle, surgical procedure, errors of refraction had no significant association with successful surgical outcome. Conclusion Both the RR and RP procedures exhibit comparable effectiveness in treating basic-type X (T). Plication may be chosen as a substitute tightening technique due to its additional benefits over resection. Poor Preoperative control of deviation decreased the chances of a successful outcome.